Determinação de isótopos estáveis de carbono e de parâmetros físico-químicos para controle de contaminação em águas superficiais e subterrâneas próximas a um aterro sanitário - Engelmann, Pâmela de Medeiros (2017)
In Brazil, landfills are the unic form of final waste disposal that being still permitted by law. However, the leachate produced during the organic matter decomposition process has a complex composition and can cause contamination of the surface and groundwater of the landfill region. Thus, the monitoring of these areas is extremely important for the characterization of the leachate produced and to avoid environmental damages. Thus, the present study had the objective of monitoring the area of a Brazilian landfill using conventional parameters (metals, anions, ammonia and physicochemical parameters), stable isotopes of dissolved inorganic carbon (δ13C-DIC) and dissolved organic carbon (δ13C-DOC) allied to multivariate analysis techniques. Samples of raw leachate, leachate of stabilization lagoons, groundwater and surface water adjacent to the landfill were characterized. The conventional and alternative parameters together with the multivariate analysis showed that old cell (C3) is in a more advanced process of stabilization of the organic matter, probably already in the methanogenic phase. The data show that the organic matter stabilization lagoons are being efficient, improving the quality of the leachate. The values found for alkali metals, nitrate and chloride indicate contamination in one of the groundwater monitoring wells (PZ3) and, moreover, the sand extraction area (BG1) present at the side of the landfill study also show variation when compared with local white. Thus, isotopic ratio data for groundwater and surface waters were important to confirm the presence of contamination at the PZ3 and BG1 sampling sites, since an isotopic enrichment of the δ13C-DIC was observed at these sites.